A pilot study of cardiac guided wave elastography: an ex vivo testing in a rodent model with mechanical testing validation - Liu, Jingfei; Corporan, Daniella; Vanderlaan, Don; Padala, Muralidhar; Emelianov, Stanislav Y. (Frontiers in Acoustics, 2024)
Many heart diseases can change the elasticity of myocardial tissues, making elastography a potential medical imaging strategy for heart disease diagnosis and cardiovascular risk assessment. Among the existing elastography methods, ultrasound elastography is an appealing choice because of ultrasound's inherent advantages of low cost, high safety, wide availability, and deep penetration. The existing investigations of cardiac ultrasound elastography were implemented based on a bulk model of heart tissue, treating the waves generated in the myocardial tissues as shear waves. In this pilot study, we considered the distinct geometric characteristics of heart tissue, i.e., being a layered structure and its dispersive nature as biological tissue. Based on these considerations, we modeled heart tissues as a layered-dispersive structure and developed a new ultrasound elastography method, ultrasonic guided wave elastography, to characterize the myocardial elasticity. The validity of this layered-dispersive model and the reliability of the developed guided wave elastography were first verified on tissuemimicking phantoms. Then, the guided wave elastography was applied to an ex vivo imaging of a rat heart tissue specimen in real-time during the biaxial planar mechanical testing. The comparison of the real-time myocardial elasticity obtained from guided wave elastography and mechanical testing demonstrated strong matching, verifying the reliability of the developed cardiac guided wave elastography as a potential method for characterizing myocardial elasticity.